2002
DOI: 10.1037/1076-898x.8.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation skill in a real-world task: Measurement, training, and transfer in tennis.

Abstract: Anticipation skill in tennis was examined using realistic film simulations, movement-based response measures, and a portable eye movement recording system. Skilled players were faster than their less skilled counterparts in anticipating the direction of opponents' tennis strokes, with this superior performance being based, at least in part, on more effective visual search behaviors. The processes mediating superior performance were then modeled in groups of recreational tennis players using video simulation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
301
2
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 276 publications
(333 citation statements)
references
References 32 publications
21
301
2
9
Order By: Relevance
“…However, the expert players had significantly longer fixation durations and final fixations compared to the novice players, supporting previous research. Their average final fixation of 1700 ms corresponded well with the duration of the execution phase, which was an average of 1900 ms. Data support previous research on moderately consistent and controlled tasks (Abernethy et al, 2008;Williams et al, 2002) showing fixations of a longer duration are indicative of expert performance. It is possible that the longer fixation duration allowed the expert group more time to extract information from the kinematic cues emanating from the opponent's body.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, the expert players had significantly longer fixation durations and final fixations compared to the novice players, supporting previous research. Their average final fixation of 1700 ms corresponded well with the duration of the execution phase, which was an average of 1900 ms. Data support previous research on moderately consistent and controlled tasks (Abernethy et al, 2008;Williams et al, 2002) showing fixations of a longer duration are indicative of expert performance. It is possible that the longer fixation duration allowed the expert group more time to extract information from the kinematic cues emanating from the opponent's body.…”
Section: Discussionsupporting
confidence: 87%
“…As predicted, the expert participants were significantly more accurate at anticipation on the temporal occlusion test compared to the novice participants. Findings support previous research showing that expert athletes are better than novice athletes at anticipating upcoming actions (Abernethy, Gill, Parks, & Packer, 2001;Dicks, Button, & Davids, 2010;Gabbett, Rubinoff, Thorburn, & Farrow, 2007;Muller, Abernethy, & Farrow, 2006;Savelsbergh et al, 2002;Williams et al, 2002), especially earlier in the execution of the action (Abernethy, 1990;Williams et al, 2002). The expert group have a significantly greater amount of domain specific experience, thus enabling them to combine the current environmental situation with those previous experiences to aid in response selection (Causer et al, 2012), whereas the novices do not.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Three search rate measures were calculated: the mean number of fixations, the mean number of areas fixated on, and the mean fixation duration for each trial (Williams, Ward, Knowles, & Smeeton, 2002). Fixation/tracking behavior was coded when gaze remained within 3Âș of visual angle of a location or moving object Percentage viewing time.…”
Section: Gaze Behaviorsmentioning
confidence: 99%
“…Williams et al (2002) have shown that the slow replay presentation of video accompanied by verbal instruction can contribute to raising the predictive ability of beginner tennis players, but the effectiveness of the verbal instruction and video presentations has not been fully verified in many other studies. This is because even if a player has participated in the experiments of a cognitive training program for raising the predictive abilities, the control of the conditions is difficult; therefore, the direct effects of training cannot be verified (Williams et al 2004).…”
Section: Introductionmentioning
confidence: 99%